The Erbisberg drilling 2011: Implications for the structure and postimpact evolution of the inner ring of the Ries impact crater. (15th April 2019) - Arp, Gernot; Reimer, Andreas; Simon, Klaus; Sturm, Sebastian; Wilk, Jakob; Kruppa, Corina; Hecht, Lutz; Hansen, Bent T.; Pohl, Jean; Reimold, Wolf Uwe; Kenkmann, Thomas; Jung, Dietmar
Abstract: The 26 km diameter Nördlinger Ries is a complex impact structure with a ring structure that resembles a peak ring. A first research drilling through this "inner crystalline ring" of the Ries was performed at the Erbisberg hill (SW Ries) to better understand the internal structure and lithology of this feature, and possibly reveal impact‐induced hydrothermal alteration. The drill core intersected the slope of a 22 m thick postimpact travertine mound, before entering 42 m of blocks and breccias of crystalline rocks excavated from the Variscan basement at >500 m depth. Weakly shocked gneiss blocks that show that shock pressure did not exceed 5 GPa occur above polymict lithic breccias of shock stage Ia (10–20 GPa), with planar fractures and planar deformation features (PDFs) in quartz. Only a narrow zone at 49.20–50.00 m core depth exhibits strong mosaicism in feldspar and 10 1 ¯ 2 PDFs in quartz, which are indicative of shock stage Ib (20–35 GPa). Finally, 2 m of brecciated Keuper sediments at the base of the section point to an inverse layering of strata. While reverse grading of clast sizes in lithic breccias and gneiss blocks is consistent with lateral transport, the absence of diaplectic glass and melt products argues against dynamic overthrusting of material from a collapsing central peak, as seen in the much larger Chicxulub structure. Indeed, weakly shocked gneiss blocks are rather of local provenance (i.e., the transient crater wall), whereas moderately shocked polymict lithic breccias with geochemical composition and 87 Sr/ 86 Sr signature similar to Ries suevite were derived from a position closer to the impact center. Thus, the inner ring of the Ries is formed by moderately shocked polymict lithic breccias likely injected into the transient crater wall during the excavation stage and weakly shocked gneiss blocks of the collapsing transient crater wall that were emplaced during the modification stage. While the presence of an overturned flap is not evident from the Erbisberg drilling, a survey of all drillings at or near the inner ring point to inverted strata throughout its outer limb. Whether the central ring of the Ries represents remains of a collapsed central peak remains to be shown. Postimpact hydrothermal alteration along the Erbisberg section comprises chloritization, sulfide veinlets, and strong carbonatization. In addition, a narrow zone in the lower parts of the polymict lithic breccia sequence shows a positive Eu anomaly in its carbonate phase. The surface expression of this hydrothermal activity, i.e., the travertine mound, comprises subaerial as well as subaquatic growth phases. Intercalated lake sediments equivalent to the early parts of the evolution of the central crater basin succession confirm a persistent impact‐generated hydrothermal activity, although for less time than previously suggested.